Online Media Framing of the East Java MUI Fatwa on ‘Sound Horeg’ - Anwari; Syahirul Alim; Shahril Anuar Abdul Ghalim; Muhammad Irawan Saputra (Mediakita, 2026)
This study investigates how digital media construct news narratives surrounding the East Java MUI Fatwa on Sound Horeg using Robert N. Entman’s (1993) framing analysis model. It offers a novel contribution by examining how various online media platforms frame a religious issue with substantial social implications, and how these frames potentially shape public opinion in the digital era. The research analyzes ten national and local online news outlets that reported on the fatwa between July and August 2025, including MUI.or.id, Detik.com, Beritajatim.com, Kontan.co.id, BBC Indonesia, CNBC Indonesia, Kompas.com, Hidayatullah.com, iNews Surabaya, and Kompas.id. Findings reveal three dominant framing patterns: (1) normative-religious, which emphasizes moral and sharia-based legitimacy; (2) policy-technical, focusing on regulatory aspects such as volume and time restrictions; and (3) dialogical-critical, which encourages public debate and negotiation. By integrating framing theory with agenda-setting and social construction of reality perspectives, the study demonstrates how media narratives can influence issue salience and diversify public perspectives. These insights enrich mass communication research, especially by helping to understand the role of media in framing religious topics in contemporary digital discourse.